THE IMPROVEMENT OF SKILL IN QUESTIONING THROUGH THE APPLICATION OF LEARNING STARTS WITH A QUESTION STRATEGY - Yuniarti Yuniarti; Sukarno Sukarno; Sularmi Sularmi (Universitas Sebelas Maret, 2018)
The objectives of this research is to improve and describe the results of the improvement of questioning skills through the application of Learning Starts With a Question strategy in 5th grade students of SD Negeri Tegalayu No. 96 Surakarta. The subjects of this research are teachers and students of 5th grade of SD Negeri Tegalayu which are 20 students. The techniques of collecting data are in the form of test, observation, interview, and documentation. The data validity used is triangulation source and triangulation technique. The data analysis uses Miles and Huberman interactive analysis model. The results of this research indicate that the improvement of questioning skills through the application of Learning Starts With a Question strategy in each cycle is 70% in cycle I it increases to 95% in cycle II. The conclusion of this research is the application of Learning Starts With a Question strategy can improve the questioning skill of 5th grade students of Elementary School.